Reimagining Catholic Peacebuilding Through Pope Francis's "Culture of Encounter": The Case of Nigeria's Niger Delta Region - Martin Owhorchukwu Ejiowhor (Journal of Moral Theology)
The document _Pacem in Terris_ (PT) represents a pivotal moment in the history of Catholic social teaching, both at the level of the universal church and local churches. PT asserts that the church has a moral duty to contribute to global peace, to be founded on the principles of truth, justice, charity, and freedom, in imitation of Christ the Prince of Peace. This article argues that Pope Francis’s “culture of encounter” (CoE) significantly advances this moral obligation, which it conceives as constitutive of the church’s evangelizing mission, to contribute to sustainable just peace through social dialogue and active nonviolence incorporating well-coordinated peace advocacy while reimagining the conceptualization of conflict and peacebuilding processes. The article uses a literature review to examine two key questions: firstly, how Francis conceptualizes conflict in light of the CoE; and secondly, the practical implications of the CoE for rethinking Catholic peacebuilding strategies, especially in Nigeria’s Niger Delta region. In conclusion, the article demonstrates how Pope Francis’s papacy integrates teaching and praxis in the church’s promotion of global peace. The “culture of encounter” calls for reinvigorated ecclesial self-identity and prophetic witness, essential for the church’s active contribution to global conflict transformation and sustainable social peace.